Politik Kekerasan (Para Jagoan) dan Dendam di Bali - I Ngurah Suyawan (Antropologi Indonesia, 2009)
Violent tragedy in Bali has a long history. Violence during the Dutch colonial regime, until the 1965 massacre of local political violence under the "Orde Baru" occurred. Post-Reform of 1998, the tragedy of violence re-emerged in tandem with the strengthening of indigenous authority (Pakraman Village) that forced silence during the centralized authoritarian "Orde Baru" regime. Pakraman village go hand in hand with the spirit of strengthening the cultural movement (Ajeg Bali) post Bali bombings of 2002 and 2005. Within institutions of Pakraman Village, there lies pecalangan, a traditional indigenous security forces who participates in the business of security and control of new settlers in these territories. In political violence contestation and strengthening of the culture, the local-hero who has a long history of political violence in Bali plays their vital role through the mass organizations and also joined as pecalangan. This paper tried to describe the relationship between political history of violence in Bali and the pursuit of the local-hero in it. Key words: Political violence, Ajeg Bali, Pecalangan, Pakraman Village, Local-hero